How do organisations generate and distribute value? Stakeholder value as the aim of the New Business Narrative [NBN] and Stakeholder Accounting [SA] as an information tool - José Luis Retolaza Ávalos; Leire San-Jose; R. Edward Freeman (Boletín de Estudios Económicos)
Many different companies have decisively embraced the New Business Narrative focused on the Stakeholder Theory and it has been part of the ethos of leading companies worldwide for some time now. However, a systematic process has not been developed to identify an organisation’s withdrawn or distributed value for its different stakeholders in monetary terms. Accounting is inadequate for this purpose and the current information system therefore needs to be expanded. This article reflects on Stakeholder Accounting [SA]. Based on the multi-faceted model, it proposes broadening the value concept to also include price-based transactions, transfers performed in a non-market environment (and without consideration), and emotional ones. Moreover, it proposes expanding from a one-dimensional perspective, focused on shareholders, to a multi-dimensional including all the stakeholders of the organisation. The rest of the article reflects on the multiple experiences generated over the last ten years, along with the applicability, the potential and the implications of this accounting both for organisations and for their stakeholders.